Early abstractions, numbers 1-5, 7 & 10 & Mirror animations, number 11 (1941-1957) - Smith, Harry ([Santa Monica, CA] : Harry Smith Archives, 2007)
Early abstractions are hand painted animated images set to a soundtrack of Beatles songs Mirror animations no. 11 is composed of cut up animation and collage techniques, set to Thelonius Monk's Mysterioso
Onderzoek KASK Professioneel (OFVP)
film
Keywords: Smith, Harry